PSXVII-4 A comparison of weighted gene co-expression networks in high- and low-feed efficiency dairy cattle. (7th December 2018) - Seymour, D; Miglior, F; Fonseca, P; Lam, S; Brito, L; Suárez-Vega, A; Cánovas, A
Abstract: Feed efficiency is a trait of growing importance in the field of dairy cattle breeding as feed is often the single largest expense in dairy production systems. However, biological underpinnings of this trait have yet to be definitively characterized. The objective of this study was to identify gene networks that exhibited correlated expression patterns in dairy cattle classified as either high- or low-feed efficiency based on residual feed intake (RFI; kg/d). Data used for analyses was obtained from a previous study and accessed through a publicly-available repository (NCBI GEO: GSE92398). Transcriptome data generated using RNA-Sequencing technology was available from two sets of liver biopsies performed on 19 dairy cattle (10 Jersey & 9 Holstein). Animals of both breeds were selected from a research herd based on extreme RFI and allocated to two groups: HIGH feed efficiency (Holstein [n = 5], Jersey [n = 5]) and LOW feed efficiency (Holstein [n = 4], Jersey [n = 5]). Weighted gene co-expression networks (WGCN) were estimated using the WGCNA package in R for high- and low-feed efficiency groups to identify modules of co-expressed genes exclusively present in either of the groups. Twenty-nine and 38 modules were identified as uniquely co-expressed in high- and low-feed efficiency groups, respectively. In the high-feed efficiency group, modules of co-expressed genes were composed of 4336 genes that play crucial roles in biological processes related to feed efficiency, such as regulation of mitochondrial metabolism. In the low-feed efficiency group, 3940 genes responsible for regulation of carbohydrate and protein absorption were found to be in networks differentially co-expressed vs. high efficiency group co-expression networks. Genes involved in uniquely co-expressed networks and the positional markers located within those candidate genes will be further analyzed to elucidate functional relationships of these genes and how they contribute to feed efficiency in dairy cattle.